INFORMATION SOCIETY: FORECASTS OF SOCIAL TRANSFORMATIONS AND REALITY - Bronnikova, Larysa (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. At the end of the ХХ century, scientists from various countries began to use the name "information society" to define social reality. In the time that has passed since the emergence of the main paradigms of the information society, not all of its characteristics have turned out to be universal. In addition, the features of reality and the ideal are intertwined in ideas about the information society. That is why the new signs of modern social activity require clarification. The aim of the article is an attempt to compare the features, characteristics, and phenomena of the modern information society with the image of society that was formed in the last decades of the ХХ century on the basis of numerical concepts of the information society. Research methodology is a complex of philosophical and general scientific methods. The article also uses sociocultural, systemic and synergistic approaches. Research results. The information age has become a reality from the project. But scientists continue to compare the forecasts of the authors of the concepts of the information society, created at the end of the ХХ century, with the characteristics of today’s society. Technological changes continue, various spheres of social life are updated - production, everyday life, relations between the state and citizens. Both M. Kastels and K. Schwab note changes in the social sphere at the beginning of the ХХІ century due to the continuation of the information revolution. Discussion. Ukrainian scientists analyze the features of modern society, note the utopian nature of some forecasts regarding future development. They are trying to create an image of the information society. Conclusions. The research carried out in the article showed the role of theoretical knowledge – in this case, the concepts of the information society – in organizing our perception of reality. These concepts in their generalized form contain a theoretical basis, a methodological and terminological basis. Their authors predicted the course of historical development, which allows scientists even today to understand such a multifaceted and complex social life. In author’s opinion, the topic of discussions "Forecasts and reality" in the context of the problems of the information society will remain promising and fashionable. After all, society is dynamically developing, and the name "information society" is understood by scientists not only as a social ideal, but also as a current reality. In addition, rethinking the meaning of the concept of "information society" provides an opportunity not only to create an outline of the outlines of modern society, but also to more clearly outline the ways of future development of humanity.